An estimation-based dynamic load balancing algorithm for efficient load distribution and balancing in heterogeneous Grid computing environment - Eng, Kailun; Muhammed, Abdullah; Abdullah, Azizol; Hussin, Masnida; Hasan, Sazlinah; Mohamed, Mohamad Afendee (Springer Nature, 2022)
To realise the true potential of Grid computing, resource management is playing a crucial role. Nevertheless, due to the nature of dynamism and heterogeneity in Grid computing, Grid resource management with the capability of effective and efficient load distribution and balancing remains a challenge. In this study, a dynamic load balancing algorithm is proposed for efficient load distribution and balancing in heterogeneous Grid computing environment. Extensive simulation experiments are carried out to evaluate the effectiveness of the proposed algorithm using the most popular simulator namely GridSim. The comparative results of simulation experiments show that the proposed load balancing approach gives superior performance and outperforms contemporary load balancing approaches in the literature. The findings reveal that the proposed load balancing approach is able to effectively utilise the resources while ensuring a relatively low degree of imbalance of load when dealing with different levels of heterogeneity in a Grid computing environment.